2012
DOI: 10.1111/j.1472-765x.2012.03246.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility and genetic relatedness of bovine Stenotrophomonas maltophilia isolates from a mastitis outbreak

Abstract: Aims:  To evaluate the antimicrobial susceptibility and genetic relatedness of 11 Stenotrophomonas maltophilia isolates from an outbreak of bovine clinical mastitis in one herd and two isolates from two separate mastitis cases in two other herds. Methods and Results:  Thirteen S. maltophilia isolates were obtained from milk samples from 11 cows from three dairy herds in Japan during 2008. We tested their susceptibility to 14 antimicrobials by broth microdilution and identified their genotypes by enterobacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 12 publications
(38 reference statements)
1
17
0
Order By: Relevance
“…Both have been previously detected in dairy environments in France [52]. Stenotrophomonas maltophilia has been reported in association with an outbreak of clinical mastitis in cattle in Japan [53]. In that study the bacteria were readily cultured from milk using a method very similar to that used for this work, suggesting that the Stenotrophomonas sequences identified here may be from a species other than S. maltophilia .…”
Section: Discussionmentioning
confidence: 52%
“…Both have been previously detected in dairy environments in France [52]. Stenotrophomonas maltophilia has been reported in association with an outbreak of clinical mastitis in cattle in Japan [53]. In that study the bacteria were readily cultured from milk using a method very similar to that used for this work, suggesting that the Stenotrophomonas sequences identified here may be from a species other than S. maltophilia .…”
Section: Discussionmentioning
confidence: 52%
“…Microbiota dominance and decreased heterogeneity are proposed characteristics of mastitis-associated dysbiosis (Oikonomou et al, 2014). Stenotrophomonas spp., in particular S. maltophilia, have been occasionally isolated from mastitic quarters (Nam et al, 2009;Ohnishi et al, 2012). Predominance of Stenotrophomonas has been also reported within the milk microbiota of culture-negative mastitis samples (Kuehn et al, 2013).…”
Section: Shifts In Diversity and Composition Of Udder Microbiotamentioning
confidence: 95%
“…A previous study indicated that the closely related S. maltophilia isolates were involved in a herd outbreak of mild mastitis in cattle in Japan. 26 Stenotrophomonas maltophilia has also been found to be environmental global emerging Gram-negative bacterial pathogen that can cause various serious infections in humans. 27 Owing to their multi-antibiotic resistance, 28 infections or diseases caused by S. maltophilia would be exceptionally difficult to treat.…”
Section: Influence Of Hc Feeding On Changes In the Composition Of Milmentioning
confidence: 99%